ANALISIS KUALITAS RENCANA PROGRAM PEMBELAJARAN BERBASIS UNIVERSAL DESIGN FOR LEARNING PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Dwitya Sobat Ady Dharma (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
We often encounter lesson plans that do not accommodate student differences, use of media that is not accessible to all, lesson plans that are less contextual, do not support all learners, and lack collaboration. Related to the various facts above, the problem of teacher performance, especially in making lesson plans becomes interesting to discuss because the success or failure of inclusive learning depends on the quality of the lesson plans. This research uses content analysis method with mixed method. The approach used is a case study approach, because what is studied is a number of subjects that have specificities, events, actual conditions of circumstances or situations. The data used are four lesson plans written by Tumbuh High School (THS) teachers who study History, Geography, Social Sciences, and Civics. The lesson plan is analyzed to determine the quality in terms of the completeness of the lesson plan components, the compatibility between the lesson plan components, the feasibility of learning objectives, the formulation of learning objectives, the selection and organization of teaching materials, the feasibility of learning activities, the selection of learning resources, the feasibility of evaluating learning outcomes. Data collection techniques used are documentation and interviews. Based on the results of the study, the quality of RPP 1 was classified as good with a score of 71.15%, the quality of RPP 2 was classified as very good with a score of 86.61%, the quality of RPP 3 was classified as very good with a score of 96.15%, and the quality of RPP 4 was also classified as very good with a total score of 76.92%. These four RPPs generally conform to and follow the rules of the UDL principle, which is to consider representation, action & expression, and engagement. Keyword: learning planning, social studies learning